Sox9-Increased miR-322-5p Facilitates BMP2-Induced Chondrogenic Differentiation by Targeting Smad7 in Mesenchymal Stem Cells - Yongsheng Zeng; Chengcheng Du; Pengcheng Xiao; Yiting Lei; Piao Zhao; Zhenglin Zhu; Shengqiang Gao; Bowen Chen; Shengwen Cheng; Wei Huang; Chen Zhao (Stem Cells International)
Bone morphogenetic protein 2 (BMP2) induces effective chondrogenesis of mesenchymal stem cells (MSCs) by promoting Sox9 expression. However, BMP2 also induces chondrocyte hypertrophy and endochondral ossification by upregulating Smad7 expression, which leads to the disruption of chondrogenesis. In addition, Smad7 can be inhibited by Sox9. Therefore, the underlying mechanism is not clear. Currently, an increasing number of studies have shown that microRNAs play a pivotal role in chondrogenic and pathophysiological processes of cartilage. The purpose of this study was to determine which microRNA is increased by Sox9 and targets Smad7, thus assisting BMP2 in maintaining stable chondrogenesis. We found that miR-322-5p meets the requirement through next-generation sequencing (NGS) and bioinformatic analysis. The targeting relationship between miR-322-5p and Smad7 was confirmed by dual-luciferase reporter assays, qPCR, and western blotting (WB). The in vitro study indicated that overexpression of miR-322-5p significantly inhibited Smad7 expression, thus causing increased chondrogenic differentiation and decreased hypertrophic differentiation, while silencing of miR-322-5p led to the opposite results. Flow cytometry (FCM) analysis indicated that overexpression of miR-322-5p significantly decreased the rate of early apoptosis in BMP2-stimulated MSCs, while silencing of miR-322-5p increased the rate. A mouse limb explant assay revealed that the expression of miR-322-5p was negatively correlated with the length of the BMP2-stimulated hypertrophic zone of the growth plate. An in vivo study also confirmed that miR-322-5p assisted BMP2 in chondrogenic differentiation. Taken together, our results suggested that Sox9-increased miR-322-5p expression can promote BMP2-induced chondrogenesis by targeting Smad7, which can be exploited for effective tissue engineering of cartilage.